Implementation of the Principle of Comparability in Islamic Education Learning Practices in Madrasahs - Ridho Dwi Putra; Muhammad Ali Murtadho; Saipul Annur; Ade Rosad (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study aims to analyze the application of the principle of comparability in Islamic Religious Education and its implications for improving students' understanding and shaping their Islamic character at MAN 1 Pangkalpinang City. This study uses a qualitative approach with a case study method conducted in a leading madrasah with heterogeneous student characteristics. Data were collected through in-depth interviews, participatory observation, and documentation, involving 12 informants consisting of teachers, the principal, the vice principal for curriculum, and students. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana through reduction, presentation, and simultaneous data conclusion drawing. The results showed that the principle of comparability was applied through differentiated learning strategies, proportional fairness-based assessment, and Islamic values-based curriculum collaboration. The application of this principle was proven to improve religious understanding and shape students' character to be fair, moderate, and have good morals, although there were still obstacles in the form of teachers' narrow perceptions of the meaning of substantive equality. This study emphasizes the importance of the principle of comparability as a principle of justice in contextual and humanistic Islamic education.